Task Based Learning and Teaching (TBLT) in Teaching Writing - Andi Rizki Fauzi (English Study Program University of Pasir Pengaraian, 2015)
This study was conducted to know whether there was any significant difference in the students‟ achievement in writing a descriptive text between those who are taught with “Task Based Learning and Teaching (TBLT)” and those who are taught without “Task Based Learning and Teaching (TBLT). The population of this study was taken from all of the total number of the tenth year students from X1 to X4 in SMA N 01 Kandang serang, Pekalongan in Academic year 2013/2014. The numbers of population are 85 students. Meanwhile, the samples of the study were taken from X1 class with 21 students as an experimental group and X2 class with 21 students as a control group. The experimental research was carried out using quasi-experimental design and to analyze the data independent sample t-test and paired sample t-test of SPSS program was used. Based on the analyses, the significant value of post-test score using independent t-test both of the group showed 0,001 lower than 0,05. In addition, it was reinforced by the comparison between t-value and t-table which showed t value > t table (6,083 >1,68) so that working hypothesis is accepted and null hypothesis is rejected. It could be concluded that there was significant improvement of students‟ writing mastery using TBLT.